ИССЛЕДОВАНИЕ ПРОЦЕССА ФОРМИРОВАНИЯ ВЫХОДНЫХ ИМПУЛЬСОВ МАГНИТНО-ПОЛУПРОВОДНИКОВОГО ГЕНЕРАТОРА - Волков, І.В.; Зозулев, В.И.; Подольный, С.В.; Шолох, Д.А. (Інститут електродинаміки НАН України, Київ, 2012)
The analysis of the output pulses formation in the terminating node of a magnetic-semiconductor generator (MSG) was performed. The dependencies of amplitude and pulse rise time of current in an active-inductive load from values capacitance of CK, shunt RLload, was defined. The capacitance at which the current pulse rise time is minimal, or the amplitude of pulse and invested in load power is maximum, and capacitance CK at which takes into account the total allowable limit of current pulse amplitude and duration of its front is determinate. The results of the analysis checked by experimental data. References 7, figures 7.